Subarachnoid-pleural fistula in a patient with blunt chest trauma - Szlachcińska, Aleksandra; Kozak, Agnieszka (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
A case of a 33-year-old patient with bilateral ribs fracture, left scapular bone fracture, bilateral pneumothorax, pneumomediastinum, subcutaneous emphysema after blunt chest trauma, jaw fracture and left ulna fracture is reported. In imaging studies pneumorrhachis at the level of the neck and pneumocephalus were identified. Etiology, pathogenesis, diagnosis and treatment in patients with posttraumatic pleural-subarachnoid fistula are described.